The Influence of Health Education with the Lecture Method on the Level of Knowledge About Reproductive Health - Feti Fajri Khayatul Mei; Ikit Netra Wirakhmi; Tin Utami (PROMOTOR, 2023)
Reproductive health is a healthy condition that concerns the system, function, and process of reproduction in adolescents. Adolescents need to gather knowledge about reproductive health to avoid unwanted pregnancies, be protected from Sexually Transmitted Infections (STIs), and grow into sexually healthy adolescents. The purpose of the study was to determine the effect of health education with the lecture method on reproductive health. Research method using the type of pre-experimental research design with a one-group pre-post-test design approach. The study was conducted at SMK Ma'arif NU 1 Cilongok with a grade 12 population of 407 students and a sample of 202 students using cluster random sampling techniques. The instruments used in this study were questionnaires. Data processing editing, scoring, coding and tabulating, data analysis using non-parametric tests with Wilcoxon Signed Rank Test. The results were obtained from as many as 174 respondents with a good category (86.1%) and 28 respondents with a sufficient category (13.9%). The Wilcoxon test found that there was an influence of health education with the lecture method on the level of knowledge about reproductive health at SMK Ma'arif NU 1 Cilongok p value 0.000 (<0.05). The conclusion is that health education with the lecture method influences the level of knowledge about reproductive health in students at SMK Ma'arif NU 1 Cilongok.